Analisis Ergonomi Pada Praktikum Pembubutan Mesin Dengan Pendekatan OWAS & RULA di Bengkel Fakultas Teknik UM - Sari, Cindy Puspita; Istiqomah, Mutiara Titian; Rosalinda, Nadia; Muhammad, Naufalsyah Falah; Marji, Marji; Sulistyorini, Anita (Universitas Negeri Malang, 2024)
Body position and posture are important components in carrying out activities because poor posture and other non-ergonomic elements will interfere with the focus and accuracy of workers which have an impact on production results. Based on observations and interviews with practitioners in the UM Mechanical Engineering Faculty Workshop, there are symptoms and feelings of fatigue in the body when carrying out practicum due to the duration of work for 4 hours and the target achievement of tasks that must be completed. Therefore, this assessment aims to provide an overview of student work postures that increase the risk of musculoskeletal disorders. The methods used in this observation and measurement were the Ovako Work Posture Analysis System (OWAS) and Rapid Upper Limb Assessment (RULA). The results of the OWAS score analysis showed a value of 2 in postures 1 and 2 where this attitude is harmful to the musculoskeletal system, so it needs improvement in the future, and a value of 1 in posture 3 where this attitude does not need improvement. Meanwhile, the results of the RULA score analysis showed a value of 6 high categories in postures 1 and 2 which interpret further investigation, immediate changes, as well as a value of 4 medium categories in posture 3 which can interpret further investigation, changes may be needed. Therefore, it can be concluded that there is a need to improve work postures by practitioners on tuning machines by changing work positions to ergonomic, stretching periodically, and using Personal Protective Equipment (PPE).